STRUCTURAL AND FUNCTIONAL CHARACTERIZATION OF ECO-FRIENDLY BIOSURFACTANT LIPOPEPTIDES AND THEIR CYTOTOXICITY EVALUATION FOR ENVIRONMENTAL AND PHARMACEUTICAL APPLICATIONS - RITU BALA; SOURBH SUREN GARG; ARUN KARNWAL; RATTAN DEEP SINGH (Asian Journal of Pharmaceutical and Clinical Research, 2026)
Objectives: This study compares biosurfactants produced by Bacillus subtilis microbial type culture collection 2423 (OBS), Bacillus spp. RZ2MS9 (O10), Enterobacter spp. TSSAS2-48 (O16), and standard surfactin based on their structural characteristic and cytotoxicity profile to evaluate their suitability for pharmaceuticals and environmental applications. Methods: Structural components of the biosurfactants were analyzed using thin-layer chromatography (TLC) and Fourier-transform infrared spectroscopy (FTIR), enabling identification of functional groups such as amines, fatty acids, and ester linkages. Cytotoxicity was assessed using the MTT assay on L929 fibroblast cells to determine IC50 values for each biosurfactant and the surfactin standard. Results: TLC and FTIR analyses revealed that the biosurfactants contained core structural units such as amines, fatty acids, and ester linkages, confirming their characteristic surface-active properties. The IC50 values obtained were 108.14±0.45 μg/mL (OBS), 160.70±0.21 μg/mL (O10), 214.61±0.54 μg/mL (OBS cream), 239.83±0.30 μg/mL (O10 cream), and 349.72±0.23 μg/mL (surfactin). Comparative analysis indicated that O10 demonstrated a more favorable cytotoxicity profile, suggesting higher biocompatibility. Conclusion: Bacillus spp. RZ2MS9 (O10) demonstrates promising structural and biocompatibility attributes, supporting its potential for pharmaceutical and environmental applications. Further optimization and scale-up could enhance its commercial viability.